Antifungal activity of eumelanin-inspired indoylenepheyleneethynylene against Cryptococcus neoformans - Conn, Brittney N.; Lieberman, Jacob A.; Chatman, Priscilla; Cotton, Kaitlyn; Essandoh, Martha A.; Ebqa’ai, Mohammad; Nelson, Toby L.; Wozniak, Karen L. (Frontiers in Microbiology, 2024)
Cryptococcus neoformans is an opportunistic fungal pathogen that causes meningitis in >152,000 immunocompromised individuals annually, leading to 112,000 yearly deaths. The four classes of existing antifungal agents target plasma membrane sterols (ergosterol), nucleic acid synthesis, and cell wall synthesis. Existing drugs are not highly effective against Cryptococcus, and antifungal drug resistance is an increasing problem. A novel antimicrobial compound, a eumelanin-inspired indoylenepheyleneethynylene, EIPE-1, was synthesized and has antimicrobial activity against Gram-positive bacteria, including methicillin-resistant S. aureus (MSRA), but not towards Gram-negative organisms. Based on EIPE-1's antibacterial activity, we hypothesized that EIPE-1 could have antifungal activity. For these studies, we tested EIPE-1 against C. neoformans strain H99 and 6 additional cryptococcal clinical isolates. We examined antifungal activity, cytotoxicity, effects on fungal gene expression, and mechanism of action of EIPE-1. Results showed that EIPE-1 has fungicidal effects on seven cryptococcal strains with MICs ranging from 1.56 to 3.125 μg/ml depending on the strain, and it is non-toxic to mammalian cells. We conducted scanning and transmission electron microscopy on the exposed cells to examine structural changes to the organism following EIPE-1 treatment. Cells exposed displayed structural changes to their cell wall and membranes, with internal contents leaking out of the cells. To understand the effect of EIPE-1 on fungal gene expression, RNA sequencing was conducted. Results showed that EIPE-1 affects several processes involved stress response, ergosterol biosynthesis, capsule biosynthesis, and cell wall attachment and remodeling. Therefore, our studies demonstrate that EIPE-1 has antifungal activity against C. neoformans, which affects both cellular structure and gene expression of multiple fungal pathways involved in cell membrane stability and viability.